2019
DOI: 10.1080/13696998.2019.1636381
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, comorbidities, and use of healthcare resources of patients with phenylketonuria: a population-based study

Abstract: Background: Phenylketonuria is a well-known disease, yet the characteristics of the affected population and their use of healthcare resources have not been comprehensively evaluated. Patient characteristics and use of resources are subjects of interest for most governments, especially for a disease included in new born screening programs. Objective: The aim of this study was to determine characteristics and use of healthcare resources of patients with phenylketonuria in the region of Catalonia. Methods: Record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Two studies (Emerson et al, 2016; Kinnear et al, 2018) included participants on or over the age of 16 although the majority included adults from the age of 18 only. Two further studies included children (Darbà, 2019; Ptomey et al, 2020). Six studies focused on ageing populations: one focused on ages 40+ years ( n = 1, 5%), one on ages 45+ years ( n = 1, 5%), three on ages 50+ years ( n = 3, 15%), and one on ages 60+ years ( n = 1, 5%).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Emerson et al, 2016; Kinnear et al, 2018) included participants on or over the age of 16 although the majority included adults from the age of 18 only. Two further studies included children (Darbà, 2019; Ptomey et al, 2020). Six studies focused on ageing populations: one focused on ages 40+ years ( n = 1, 5%), one on ages 45+ years ( n = 1, 5%), three on ages 50+ years ( n = 3, 15%), and one on ages 60+ years ( n = 1, 5%).…”
Section: Resultsmentioning
confidence: 99%
“…Jahja et al [ 9 ] reported that adolescent and adult PKU patients demonstrated poorer social cognition and had poorer social skills than controls, with a tendency towards lower or delayed autonomy [ 10 ] and emotional difficulties related to maintaining a PKU diet [ 11 ]. Moreover, patients often feel social isolation and limits on socialisation [ 12 ], with many of them identified as having significant neurocognitive, mental health and general health problems [ 7 , 10 , 13 , 14 ]. An association between parent stress, anxiety, and depression in parents of PKU children has also been described [ 12 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%